2017
DOI: 10.20524/aog.2017.0164
|View full text |Cite
|
Sign up to set email alerts
|

The role of endovascular therapy in acute mesenteric ischemia

Abstract: BackgroundEndovascular therapy, including aspiration thrombectomy and local thrombolytic therapy, often associated with angioplasty and stent placement, has been described in the literature. The purpose of this study was to review case series of patients with acute mesenteric ischemia treated with endovascular therapy and evaluate their outcomes.MethodsAn online review using PubMed was carried out to identify all English articles about this topic in the time interval from 2005 to 2016.The following variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Technical success was high at 100% (33/33), similar to previously reported data [9]. Stents were placed in 28/33.…”
Section: Resultssupporting
confidence: 87%
“…Technical success was high at 100% (33/33), similar to previously reported data [9]. Stents were placed in 28/33.…”
Section: Resultssupporting
confidence: 87%
“…The application of a funnel-shaped aspiration catheter may also be beneficial during acute thromboembolic occlusion of vessels other than cerebral arterial vessels, like mesenteric arteries. Commonly, no stent-retriever is used during endovascular recanalization in acute mesenterial ischemia; the clot is removed through aspiration with a so called aspiration catheter, only 23 . The use of an aspiration catheter with a self-expanding funnel-shaped tip would occlude the vessel, enabling easier aspiration and diminishing the risk of clot migration.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in recent single-center studies and systematic reviews, the recommendation for endovascular therapy first has been suggested: endovascular interventions improve mortality, lowers length of hospitalization and transfusion requirements, lowers rates of pneumonia and sepsis and decrease cost of care. 8,[23][24][25] In Europe, the ESTES guidelines created in 2016 10 aimed to improve outcomes for patients with AMI. Despite a lack of randomized controlled trials for the management of AMI, recommendations regarding diagnosis, treatment, and follow-up are given at various levels of evidence, including the use of contrast-enhanced computed tomography angiography of the abdomen/pelvis, use of broadspectrum antibiotics, use of endovascular or open embolectomy, use of systemic anticoagulation, and supportive intensive care unit measures.…”
Section: Discussionmentioning
confidence: 99%